The Union as Employer: Personnel Practices in Canadian Labour Unions - Clark, Paul; Gray, Lois; Solomon, Norm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
This paper reports on personnel practices in unions operating in Canada. The analysis is based on survey data collected from a représentative sample of 60 labour organizations. The findings indicate that for the overall sample, formai, written personnel policies are the exception and not the rule in Canadian unions. The data also reveal, however, that personnel practices are conducted on a more formai, sophisticated basis for Canadian unions with over 50,000 members. The results confirm findings of an earlier study of U.S. unions that there is a relationship between size and sophistication of administrative practices in at least this one area. This "economy of scale" effect has important ramifications for the efficient opération of unions and for the future structure of the labour movement in North America.